2009
DOI: 10.1021/jp902536t
|View full text |Cite
|
Sign up to set email alerts
|

Interactions and Aggregations in Aqueous and Brine Solutions of Poly(diallydimethylammonium chloride)/Sodium Bis(2-ethylhexyl) Sulfosuccinate

Abstract: The interactions between the anionic surfactant sodium bis(2-ethylhexyl) sulfosuccinate (AOT) and the polycation poly(diallydimethylammonium chloride) (PDDAC), the aggregations of AOT and PDDAC-bound AOT in PDDAC/AOT aqueous solutions, and the influence of salt on the interactions and aggregations have been studied by isothermal titration calorimetry (ITC), dynamic light scattering (DLS), and negative staining transmission electron microscopy (TEM). The adsorptions of AOT onto PDDAC and the formations of PDDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…It has been reported that the interaction between sulfonate and primary amino groups in a polyelectrolyte complex is stronger than that with quaternary ammonium groups . In fact, the ε-PL/BEHS complex is a water-insoluble complex; however, the PDADMACl/BEHS complex is a small micellar complex that dissociates at low BEHS concentration . These findings imply a stronger interaction between sulfonate and a primary amino group than with a quaternary ammonium group.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been reported that the interaction between sulfonate and primary amino groups in a polyelectrolyte complex is stronger than that with quaternary ammonium groups . In fact, the ε-PL/BEHS complex is a water-insoluble complex; however, the PDADMACl/BEHS complex is a small micellar complex that dissociates at low BEHS concentration . These findings imply a stronger interaction between sulfonate and a primary amino group than with a quaternary ammonium group.…”
Section: Resultsmentioning
confidence: 94%
“…23 In fact, the ε-PL/BEHS complex is a water-insoluble complex; 11 however, the PDADMACl/BEHS complex is a small micellar complex that dissociates at low BEHS concentration. 24 These findings imply a stronger interaction between sulfonate and a primary amino group than with a quaternary ammonium group. The stronger interaction between L-SO 3 Na (sulfonate group) and ε-PL (primary amino group) than that with PDADMACl (quaternary ammonium group) may contribute to superior stress at break and a high Young’s modulus and toughness, despite the lower molecular weight of ε-PL.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the cmc can be determined from the intercept of the two linear extrapolations of each half of the plot, and the enthalpy of micellization (DH mic ) can be obtained from the difference between the observed enthalpies of the two linear segments of the plots. 49,50 The values of cmc and DH mic for both surfactants in the presence and absence of BSA are given in Table S3 of ESI. † It shows that the cmc values for AOT coincides with the values measured by the other techniques used.…”
Section: Microcalorimetrymentioning
confidence: 99%
“…Here, we report on the preparation and availability of the water-insoluble complex formed by PL n + and the synthetic anionic surfactant, bis­(2-ethylhexyl) sulfosuccinate (BEHS – , is also commercialized as AOT) anion. Studies have demonstrated that the formation of a complex between BEHS – anion and a cationic compound, for example, poly­( N -ethyl-4-vinylpyridinium bromide), poly­(diallydimethylammonium chloride), and benzyldimethyltetradecylammonium, strongly suggesting that the BEHS – anion may also interact with PL n + . As expected, the water-insoluble complex was obtained, and the antimicrobial activity of the PL n + /BEHS – -complex, which is soluble in organic solvents, was investigated through coating a cellulose acetate membrane.…”
Section: Introductionmentioning
confidence: 99%